PENGARUH MOTIVASI DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI PADA PERWAKILAN BPKP PROVINSI SUMATERA SELATAN - R Roswaty; Nina Fitriana (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
This research was attempted to determine and analyze the influence of motivation and work commitment on employee performance at the BPKP Representative of South Sumatra Province. In framework of how employees can work as good as possible and employees have high motivation and commitment to work in completing work. Therefore, the objective this research was to find out the significant influence of motivation and work commitment on employee performance. The sample in this research was taken from permanent employees of the BPKP Representative of South Sumatra Province totaling 60 peoples. In analyzing the data used quantitative and qualitative analysis that contains the distribution of items from each variable, then multiple regression analysis and hypothesis testing. Based on the regression equation, the constant value of 0.543 (positive) shows that if motivation (X₁) is 0.587 and work commitment (X₂) is 0.324, it means motivation (X₁) and work commitment (X₂) have a relationship in influencing employee performance (Y) of 0.534. The result of F count is 8.651 greater than Ftable 237. So Ho was rejected and Ha was accepted, meaning that there is a significant influence between motivation and work commitment on employee performance. The correlation coefficient of 0.544 is positive, meaning that there is a correlation or relationship between the variables of motivation and work commitment to employee performance. The better the motivation and work commitment, the greater the influence on employee performance. The coefficient of determination is 0.296 (29.6%). The calculation gives the meaning that the performance variable is 29.6%. So the results of this study open opportunities for 70.6% to examine other variables outside the independent variables in this research. Keywords: Motivation, Commitment and Performance